Investors psychology on the biased investment decision: The mediating effect of extra-motivation to invest - Muhammad Zalviwan; Tulus Haryono; Hunik Sri Runing Sawitri (University of Merdeka Malang, 2020)
This study aims to prove that individual investors' psychology consisting of positive attitude, affective-self affinity, familiarity, trust, and nationalism affects investment decisions mediated by the extra motivation to invest. The data collected through questionnaires were processed and tested for the validity and reliability of the construct. Respondents in this study are individual investors who use psychological considerations as more motivation to make decisions and 404 questionnaires distributed to individual investors. This study uses Partial Least Square (PLS). It passes the fit and quality indices model criteria to determine the strength of this study's structural model before the hypothesis testing is carried out. We found four psychological variables of individual investors (positive attitude, familiarity, trust, and nationalism) that directly affect investment decisions and indirectly with the mediator of extra motivation to invest. Extra incentive to invest is not influenced by affective-self affinity and does not mediate its relationship with investment decisions. We also found that investors with psychological considerations tend to make biased decisions. Investors show behaviour that is overreaction, overconfidence, and risk tolerance (low risk with high return). JEL Classification: F52, G11, G41DOI: https://doi.org/10.26905/jkdp.v24i4.4837